Development and effect of an N-3 fatty acid-rich spread on the nutritional and cognitive status of school children - Dalton, Annalien (Stellenbosch: University of Stellenbosch, 2006)
Thesis (PhD (Food Science))--University of Stellenbosch, 2006.